Oral Administration of miR-30d from Feces of MS Patients Suppresses MS-like Symptoms in Mice by Expanding Akkermansia muciniphila - Liu, Shirong; Rezende, Rafael M; Moreira, Thais G; Tankou, Stephanie K; Cox, Laura M; Wu, Meng; Song, Anya; Dhang, Fyonn H; Wei, Zhiyun; Costamagna, Gianluca; Weiner, Howard L (Cell host & microbe, 2019)
Fecal transfer from healthy donors is being explored as a microbiome modality. MicroRNAs (miRNAs) have been found to affect the microbiome. Multiple sclerosis (MS) patients have been shown to have an altered gut microbiome. Here, we unexpectedly found that transfer of feces harvested at peak disease from the experimental autoimmune encephalomyelitis (EAE) model of MS ameliorates disease in recipients in a miRNA-dependent manner. Specifically, we show that miR-30d is enriched in the feces of peak EAE and untreated MS patients. Synthetic miR-30d given orally ameliorates EAE through expansion of regulatory T cells (Tregs). Mechanistically, miR-30d regulates the expression of a lactase in Akkermansia muciniphila, which increases Akkermansia abundance in the gut. The expanded Akkermansia in turn increases Tregs to suppress EAE symptoms. Our findings report the mechanistic underpinnings of a miRNA-microbiome axis and suggest that the feces of diseased subjects might be enriched with miRNAs with therapeutic properties.